Novel Approaches in Glucose and Lipid Metabolism Disorder Therapy: Targeting the Gut Microbiota–Bile Acid Axis - Jin Jiang; Huange Zhang; Muhammad Hussain; Abdullah; Fengqin Feng; Rongfa Guan; Hao Zhong (Biology)
Metabolic dysregulation involving glucose and lipids is closely associated with chronic diseases such as type 2 diabetes mellitus. Emerging evidence highlights the regulatory role of bile acid (BA)–gut microbiota interactions in these metabolic disorders. The gut microbiota orchestrates the biotransformation of primary BAs into bioactive secondary BAs, which function as endocrine signaling molecules by activating the nuclear farnesoid X receptor (FXR) and G protein-coupled membrane receptor (TGR5), forming a communication network essential for metabolic homeostasis. BAs also reciprocally modulate gut microbiota composition. This BA–gut microbiota co-metabolism has emerged as a promising therapeutic target for lipid metabolism disorders. This comprehensive review examines the bidirectional interplay between gut microbiota and BA metabolism, focusing on microbial transformation of BAs, host–microbial co-regulatory pathways and mechanisms of BA metabolism, and the therapeutic implications of modulating the gut microbiota–BA axis in addressing glucose and lipid metabolism disorders. The synthesis of current evidence aims to elucidate the intricate crosstalk between microbial ecology and host metabolism mediated by BA signaling pathways, thereby exploring novel therapeutic intervention strategies.